Cartilage and Muscle Cell Fate and Origins during Lizard Tail Regeneration - Londono, Ricardo; Wenzhong, Wei; Wang, Bing; Tuan, Rocky S.; Lozito, Thomas P. (Frontiers in Bioengineering and Biotechnology, 2017)
Introduction Human cartilage is an avascular tissue with limited capacity for repair. By contrast, certain lizards are capable of musculoskeletal tissue regeneration following tail loss throughout all stages of their lives. This extraordinary ability is the result of a complex process in which a blastema forms and gives rise to the tissues of the regenerate. Blastemal cells have been shown to originate either from dedifferentiated tissues or from existing progenitor cells in various species, but their origin has not been determined in lizards. As reptiles, lizards are the closest relatives to mammals with enhanced regenerative potential, and the origin of blastemal cells has important implications for the regenerative process. Hence, the aim of this study is to determine the cellular origin of regenerated cartilage and muscle tissues in reptiles using the mourning gecko lizard as the regenerative model. Methods To trace the fate and differentiation potential of cartilage during tail regeneration, cartilage cells pre-labeled with the fluorescent tracer Dil were injected into lizard tails, and the contribution of cartilage cells to regenerated tail tissues was assessed by histologic examination at 7, 14, and 21 days post-tail amputation. The contribution of muscle cells to regenerated tail tissues was evaluated using muscle creatine kinase promoter-driven Cre recombinase in conjunction with the Cre-responsive green-to-red fluorescence shift construct CreStoplight. 21 days after amputation, tail tissues were analyzed by histology for red fluorescent protein (RFP)-positive cells. Results At 7 days post-amputation, Dil-labeled cartilage cells localized to the subapical space contributing to the blastema. At 14 and 21 days post-amputation, Dil-labeled cells remained in the subapical space and colocalized with Collagen type II (Col2) staining in the cartilage tube and myosin heavy chain (MHC) staining in regenerated muscle. Lineage tracing of myocytes showed colocalization of RFP with Col2 and MHC in differentiated tissues at 21 days post-amputation. Conclusion This study demonstrates that differentiated cartilage cells contribute to both regenerated muscle and cartilage tissues following tail loss, and in turn, differentiated muscle cells contribute to both tissue types as well. These findings suggest that dedifferentiation and/or transdifferentiation are at least partially responsible for the regenerative outcome in the mourning gecko.